Interactive selection of Multivariate Features in Spatio-temporal Data and its Change depends on the selection of Object, Event, State and its 3C’s - Rathee, Sonia; Rishi, Rahul (International Journal of Computer Sciences and Engineering, 2025)
In this paper we can introduce the three metrics of the spatio-temporal database which can scrutinize the data and give us the result. And large number of applications of real world is depending on the object, event and states that are changes in day to day life. The combination of the three metrics with the vent state can convert the quantity in to quality so we can use the control point selection method. The whole process of conversion is known as appropriation. Spatio-temporal data easily become massive, either because the spatial domain contains a lot of information (satellite images) or many times the steps are available (high resolution sensor data) or both. This vignette shows how data residing in a database can be read using spatial and temporal selection and the combination of these two databases can make the output more innovative and useful.